Will Kudimaramathu make communities “think tanks” again? - Shah, Manisha; Sakthivadivel, Ramaswamy (Science Publishing Group, 2018)
Like rest of Southern India, tanks in Tamil Nadu also suffered massive deterioration as irrigation moved towards being more atomistic and less community-managed. Tank institutions declined and what remained of these irrigation tanks evolved into mostly percolation tanks. In 2017, in the face one the biggest droughts affecting the state, Tamil Nadu government announced Kudimaramathu scheme to revive the age-old practice of community participation in tank repair and management. The program has tried to bring farmers together to form WUAs to take up activities for tank rehabilitation but like many other programs in the country, these institutions appear to exist only on paper with the program being driven primarily by local PWD officers and contractors. This paper brings insights from thirty tanks under rehabilitation in seven districts of the state which were taken up under this scheme and were studied through case study approach. The study attempts to uncover the factors which led to better implementation in some tanks compared to others. The lessons derived from these tanks can form the basis for effective programs on tank rehabilitation in future, especially those which aim at making them participatory. The paper reinforces the need for empowering WUAs rather than just creating them, if tank management is to be made long-lasting.